2020
DOI: 10.1194/jlr.ra120000648
|View full text |Cite
|
Sign up to set email alerts
|

SSO and other putative inhibitors of FA transport across membranes by CD36 disrupt intracellular metabolism, but do not affect FA translocation

Abstract: Membrane-bound proteins have been proposed to mediate the transport of long-chain FA (LCFA) transport through the plasma membrane (PM). These proposals are based largely on reports that PM transport of LCFAs can be blocked by a number of enzymes and purported inhibitors of LCFA transport. Here, using the ratiometric pH indicator (2′,7′-bis-(2-carboxyethyl)-5-(and-6-)-carboxyfluorescein and acrylodated intestinal FA-binding protein-based dual fluorescence assays, we investigated the effects of nine inhibitors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 101 publications
0
18
0
Order By: Relevance
“…Evidence collected in the past years indicates that the transmembrane protein CD36 (SR-B2) serves to bring fatty acids to or from cell membranes while translocation of fatty acids between the leaflets of the lipid bilayer occurs by passive diffusion. A new contribution from Jay et al (1) published in the Journal of Lipid Research shows results of live cell experiments using fluorescent indicators, supporting the hypothesis that long-chain fatty acids diffuse rapidly across biological membranes. We argue that this additional evidence further integrates opposing models of diffusion and translocation.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Evidence collected in the past years indicates that the transmembrane protein CD36 (SR-B2) serves to bring fatty acids to or from cell membranes while translocation of fatty acids between the leaflets of the lipid bilayer occurs by passive diffusion. A new contribution from Jay et al (1) published in the Journal of Lipid Research shows results of live cell experiments using fluorescent indicators, supporting the hypothesis that long-chain fatty acids diffuse rapidly across biological membranes. We argue that this additional evidence further integrates opposing models of diffusion and translocation.…”
mentioning
confidence: 71%
“…Jay and coworkers observed that transmembrane fatty acid transport, as measured using the pH indicator BCECF, is not influenced by CD36, either with or without inhibition by SSO, although marked effects on intracellular fatty acid metabolism were observed. From these studies, the investigators concluded that fatty acids do not require an active protein transporter for their transmembrane movement and that fatty acid uptake is merely governed by a fatty acid metabolism-driven transmembrane gradient (1). However, it should be realized that BCECF records the arrival of protonated fatty acids at the inner leaflet of the membrane (the subsequent release of the proton is monitored) but not the desorption of the fatty acid from the membrane into the vesicular lumen or soluble cytoplasm (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While Mfsd2a is the reported transporter for DHA-lysoPC, it is uncertain whether DHA or other plasma unesterified fatty acids require a membrane transporter to be taken up by the brain. There is evidence indicating that uptake occurs by a diffusion mechanism that does not rely on a membrane protein transporter [ 32 , 33 , 34 ]. Other findings indicate that a membrane transporter and cytosolic fatty acid-binding protein are required for fatty acid uptake [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…While short-chain fatty acids and MCFAs can freely diffuse across the cell membrane into the cytosol, the uptake of LCFAs, which are the most abundant among the three FA types, appears to be more complex (Schönfeld and Wojtczak, 2016). Despite still being under discussion, LCFA uptake might be realized through combination of passive diffusion and protein-accelerated entry into the membrane as well as desorption at the inner side of the membrane (Glatz and Luiken, 2020;Jay et al, 2020;Thompson et al, 2010).…”
Section: Characterization Of Mature Adipocytes-on-chipmentioning
confidence: 99%